2019
DOI: 10.1590/0103-6440201802861
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Bioactive Potential of a New Epoxy Resin-based Root Canal Sealer

Abstract: The aim of this study was to evaluate physicochemical properties and bioactive potential of Sealer Plus, in comparison with MTA Fillapex, Sealapex and AH Plus. Setting time, flow, and radiopacity were evaluated based on ISO 6876 Standard. Flow was also assessed in area (mm²). The solubility and volumetric change of the sealers were evaluated after 7 and 30 days of immersion in distilled water. Solubility was evaluated by the difference in mass of materials before and after immersion. Volumetric change was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
3
11
0
6
Order By: Relevance
“…Although the flow value of AH Plus was numerically higher than Sealapex and Fill Canal, the sealers had a statistically similar flow. The high flow of AH Plus was described in previous studies 12,13,[15][16][17][18] . The greater concentration of epoxy resin in AH Plus is considered the reason for its high flow rate 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the flow value of AH Plus was numerically higher than Sealapex and Fill Canal, the sealers had a statistically similar flow. The high flow of AH Plus was described in previous studies 12,13,[15][16][17][18] . The greater concentration of epoxy resin in AH Plus is considered the reason for its high flow rate 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Ltda., Rio de Janeiro, RJ, Brazil) is a zinc oxide and eugenol-based sealer that is routinely used in the Brazilian dental practice 11 . Sealapex (SybronEndo, Glendona, CA, USA) is a root canal sealer based on calcium hydroxide 12 . Previous studies showed flow in accordance with the ISO 6876 for sealers based on calcium hydroxide, epoxy resin and zinc oxide and eugenol 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nessa condição de contato, o cimento resinoso AH Plus apresentou menor atividade antimicrobiana durante o período avaliado, fato também encontrado em estudos anteriores (Poggio, et al, 2017). O AH Plus apresenta baixos valores de pH e solubilidade (Mendes, et al, 2018;Tanomaru-Filho et al, 2019) quando comparado aos cimentos biocerâmicos, o que pode justificar sua menor ação antimicrobiana neste estudo. Os cimentos MTA Fillapex e Sealer Plus também apresentaram ação antimicrobiana significativamente maior do que o AH Plus e o controle.…”
Section: Resultsunclassified
“…Эпоксидные герметики имеют относительно короткое время полного отверждения, которое в среднем составляет 8 часов, при рабочем времени (первичного отверждения) около 4 часов [63].…”
Section: скорость отвержденияunclassified